Selective Generation of Aldimine and Ketimine Tautomers of the Schiff Base Condensates of Amino Acids with Imidazole Aldehydes or of Imidazole Methanamines with Pyruvates—Isomeric Control with 2- vs. 4-Substituted Imidazoles - Greg Brewer; Cynthia Brewer; Raymond J. Butcher; Peter Zavalij (Molecules, 2024)
The Schiff base condensation of 5-methyl-4-imidazole carboxaldehyde, 5Me4ImCHO, and the anion of an amino acid, H2N-CH(R)CO2− (R = -CH3, -CH(CH3)2 and -CH2CH(CH3)2), gives the aldimine tautomer, Im-CH=N-CH(R)CO2−, while that of 5-methylimidazole-4-methanamine, 5MeIm-4-CH2NH2, with a 2-oxocarboxylate anion, R-C(O)-CO2−, gives the isomeric ketimine tautomer, Im-CH2-N=C(R)CO2−. All are isolated as the neutral nickel(II) complexes, NiL2, and are characterized by single crystal structure determination, IR, and positive ion ESI MS. In the cases of the 4 substituted imidazoles, either 5MeIm-4-CHO or 5MeIm-4-CH2NH2, both the aldimine and ketimine complexes are isolated cleanly with no evidence of an equilibrium between the two tautomers under the experimental conditions. The aldimines are blue while the tautomeric ketimines are green. In contrast, for the 2-substituted imidazoles, with either Im-2-CHO or Im-2-CH2NH2, the isolated product from the Schiff base condensation is the ketimine, which in the solid is green, as observed for the 4-isomer. These results suggest that for the 2-substituted imidazoles, there is a facile equilibrium between the aldimine and ketimine tautomers, and that the ketimine form is the thermodynamically favored tautomer. The aldimine tautomers of the 4-substituted imidazoles have three stereogenic centers, the nickel (Δ or Ʌ) and the two alpha carbon atoms (R or S). The observed pair of enantiomers is the ɅRR/ΔSS enantiomeric pair, suggesting that this pair is lower in energy than the others and that this is in general the preferred chiral correlation in these complexes.